Approaches to pilgrimage: reading some post-Independence pilgrimage accounts in modern South Asian languages - Harder, Hans (Ritual journeys in South Asia, 2019)
In generic terms, pilgrimage accounts border on travelogues and biographies, and they are closely linked to hagiographies and genres glorifying